Implementation of ACO-Based Selection with Backward-Ant Mechanism for Adaptive Routing in Network-on-Chip Systems - Hsin, Hsien-Kai; Chang, En-Jui; Wu, An-Yeu (IEEE embedded systems letters, 2013)
The Networks-on-Chip (NoC) provides regular and scalable design architecture for the chip multiprocessor (CMP) systems. The routing efficiency dominates the overall system performance because of more complex applications and network scaling. The Ant Colony Optimization (ACO) is a distributed collective-intelligence algorithm. The ACO-based selection scheme with Backward-Ant mechanism (ACO-BANT) can provide extra feedback congestion information compared with forward-ant mechanism. However, the storing and computation cost of BANT is too high for the NoC systems. In this work, we implement the ACO-BANT selection scheme with feasible cost on NoC. The simulation results show that the proposed scheme yields improvements in saturation throughput by 16.26% compared to the OBL selection. We also implement the router architecture of the proposed scheme, which has the highest improvement-to-overhead ratio.